Developing the tissue viability seating guidelines. Issue 1 (February 2018) - Stephens, Melanie; Bartley, Carol; Betteridge, Ria; Samuriwo, Ray
Abstract: Background: Costs for the prevention and management of pressure ulcers have increased significantly with limited published advice from health and social care organisations on seating and preventing pressure ulcers. At the request of the UK Tissue Viability Society the aim of the publication was to develop a practical guide for people, carers and health and social care professionals on how the research and evidence base on pressure ulcer prevention and management can be applied to those who remain seated for extended periods of time. Methods and findings: The evidence base informing the guidelines was obtained by applying a triangulation of methods: a literature review, listening event and stakeholder group consultation. The purpose was to engage users and carers, academics, clinicians, inspectorate and charities, with an interest in seating, positioning and pressure management to: gather views, feedback, stories, and evidence of the current practices in the field to create a greater awareness of the issue. Conclusion: The new guidelines are inclusive of all people with short and long-term mobility issues to include all population groups. The document includes evidence on where pressure ulcers develop when seated, risk factors, best possible seated position and what seat adjustments are required, the ideal seating assessment, interventions, self-help suggestions and key seating outcomes. The updated TVS CPGs have been informed by the best available evidence, the insights and wisdom of experts, stakeholders and people who spend extended periods of time sitting. Highlights: A practical guide was required for people who remain seated. The guidelines were developed by applying a triangulation of methods. End user collaboration was paramount. Advanced the best possible care to prevent and treat pressure ulcers.